Images associées à l’usage du français en milieu professionnel marocain : Cas des PME
Within Moroccan SMEs, the French language has, alongside Arabic, of paramount importance. It is used to varying degrees by the executives and employees in their written communication (letter, memo, report, reporting ...), oral (telephone, meeting, interview ...) and telematic (Intranet, Extranet, e-mail ...).The objective of this research would be to cast an analytical look at internalized conceptions as well as the actual practices related to the use of the French language in Morocco workplace.For this, we will both present and interpret the results from a survey we conducted in the field in 2006/2007. There are two questionnaires respectively to SME managers and employees within three regions of the Kingdom, namely: Casablanca, Marrakech and Beni Mellal.